East Asian trends of human resource management: theories and practices - Andalib, Tarnima Warda; Mohd Ridzuan, Darun; Noor Azlinna, Azizan (Inderscience Enterprises Ltd., 2019)
In general, HRM policies are affected by assorted organisational external and internal factors and are persuaded by divergent HRM models. Usually, HRM practitioners develop HRM policies by perceiving the most favourable organisational factors and by preferring the most appropriate HRM models or the elements of HRM models. Now, for the last several years it has been observed that various researchers have constructed these HRM models. While constructing the HRM models, a few researchers have engrossed the humanitarian ground whereas others have focused on the materialistic ground. In this paper, the authors have reviewed numerous articles and collected secondary data about HRM policies, models and factors. Firstly, the authors have found the HRM factors that put impact and facilitated to build the HRM models. Secondly, they have found and discussed about a few HRM models that are discovered and recognised at different times. Thirdly, they have also reviewed several East Asian countries' HRM practices and classified the dominant factors and applied HRM models.